Hubungan Antara Intensitas Penggunaan Media Sosial Tiktok pada Citra Tubuh Remaja di Sulawesi Selatan - Annisa, Nur; Nurdin, Muh. Nur Hidayat; Tri Sulastri (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to analyze the impact of TikTok social media usage intensity on body image among adolescents in Sulawesi Selatan. In the current digital era, social media, particularly TikTok, has become a popular platform among teenagers, often showcasing visual content that can influence their perceptions of body image. The research method employed is a survey involving 223 adolescents aged 15 to 17 as respondents. Data were collected through a questionnaire measuring TikTok usage intensity and body image using. The results of the analysis showed that there was a significant negative relationship between the intensity of TikTok social media use and body image in adolescents, with a significance value of p = 0.000 or p <0.05. The correlation coefficient of -0.397 or is classified as weak and indicates that the intensity of TikTok use is negatively related to body image. This study can provide a basis for the development of psychology programs that aim to increase awareness and control in the use of social media to maintain a positive body image among adolescents.